Taxonomic revision of the Limonium cancellatum group (Plumbaginaceae) in Croatia - Bogdanović, Sandro; Brullo, Salvatore (Phytotaxa, 2015)
A taxonomic revision of the genus Limonium (Plumbaginaceae) in Croatia was carried out. In particular, the species belonging to L. cancellatum group are examined on morphological, nomenclatural, ecological and chorological grounds. The morphological study is based on herbarium materials and living plants. 26 species are recognized, of which 4 are well known in literature (L. cancellatum, L. dictyophorum, L. vestitum and L. subanfractum), while 21 species are described as new to science (L. busianum, L. cazzae, L. croaticum, L. ginzbergeri, L. issaeum, L. istriacum, L. lagostanum, L. leprosorum, L. liberianum, L. liburnicum, L. lovricii, L. milovicii, L. omissae, L. pelagosae, L. pharosianum, L. pomoense, L. subnudum, L. tabulare, L. trinajsticii, L. velutinum and L. zankii). A new combination (L. brusnicense) was also proposed. Description, iconography, type, nomenclatural data, etymology, ecology, distribution maps and taxonomical notes are given for each taxon. New somatic chromosome number was given for 4 species (L. cancellatum, L. dictyophorum, L. lovricii and L. milovicii). The phenetic tree clearly shows that the species are morphologically related and two main groups can be separated on the base of the hairness. In order to allow a correct identification, a diagnostic key is provided.